Comparison of physical and rheological properties of calcium carbonate-polypropylene composite and SBS modified bitumen - Erkus, Yunus; Kok, Baha Vural (Elsevier Sci Ltd, 2023)
In this study, applicability of calcium carbonate and polypropylene composite (PPC), which is widely used in plastics industry, in bitumen modification was investigated. The binders were tested with physical experiments (softening point, penetration, rotational viscosity, storage stability) and rheological experiments (bending beam rheometer, dynamic shear rheometer, multiple stress creep recovery). To demonstrate the advantage of PPC modification, the PPC and styrene-butadienestyrene (SBS) additived bitumen were compared considering per-formance and cost. Consequently, penetration decreased whereas softening point and viscosity increased when PPC was used in bitumen. The binder modified with 21% PPC showed twice rutting resistance of bitumen containing 3% SBS. 21% PPC, 3% SBS and 4% SBS showed similar influences on low temperature features of binder. PPC had produced bituminous binders that were resistant to deformation at medium and high temper-atures, making them appropriate for heavy traffic conditions. According to black and Cole-Cole diagrams, the 21% PPC modification was the most dominant modification of the polymeric phase and flexibility. As a result, it was found that the 21% PPC modified binder can generally be considered as an alternative to the 4% SBS modified binder in terms of performance and cost.
Keywords: Bituminous binders; Calcium carbonate and polypropylene; composite; Rheological properties; Cost; Styrene -butadienestyrene